THE APPLICATION OF LOGISTIC REGRESSION TO FIND THE FACTORS THAT INFLUENCE BRAND LOYALITY ON FAST-FOOD RESTAURANT CASE STUDY : KFC, CFC AND MC DONALD - Bonifasius MH. Nainggolan (Panorama Nusantara, 2015)
This study aims to assess the application of logistic regression to find the factors that influence brand loyalty on fried chicken fast-food restaurant and arrange logistic regression model of the determinants of brand loyalty in the fried chicken fast-food restaurant. To carry out the study authors conducted a survey through a questionnaire to a fried chicken fast-food restaurant, which is to Kentucky Fried Chicken (KFC), California Fried Chicken (CFC) and Mc Donald. The number of samples in this study there were 517 people. Sampling method on the author is non-random sampling technique (non-probability sampling technique). Before distributing questionnaires authors first tested the validity and reliability of the data with the test product moment correlation and Cronbach Alpha method. Results of the study provide information on the logistic regression model of factors that influence consumer brand loyalty in each of the fried chicken fast-food restaurant partially or after the data are combined. Partially determinants of consumer loyalty at KFC is the price, the CFC is gender, number of visits, product quality and restaurant environments, while at the restaurant Mc. Donald is the quality of service and price. Taken together, the determinants of customer loyalty in the three restaurants is the quality of products, quality of service, price and neighborhood restaurants.